Pengaruh Kompetensi Kepribadian Guru PAK Terhadap Disiplin Belajar Siswa Kelas VIII SMP Negeri 2 Nainggolan Tahun Pembelajaran 2023/2024 - Lestari Aritonang; Malani Simanungkalit; Dame Taruli Simamora; Simion D. Harianja; Taripar Aripin Samosir (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the positive and significant influence of the Personality Competence of Religious Education Teachers on the Learning Discipline of Class VIII Students of SMP Negeri 2 Nainggolan for the 2023/2024 Academic Year. The method used in this research is a quantitative research method with descriptive statistics. The population is all students in class VIII of SMP Negeri 2 Nainggolan for the 2023/2024 academic year, totaling 67 people and the sample was determined to be 67 people so it is a research population. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Personality Competence of Religious Education Teachers on the Learning Discipline of Class VIII Students of SMP Negeri 2 Nainggolan in the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.421 > rtable (a=0.05; CI=95%; n=67) = 0.244, thus it is known that there is a positive relationship between variable 05;dk=n-2=65) = 2,000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 17.7%. 3) Test the hypothesis using the t test to obtain tcount > ttable, namely 3.742 > 2.000. Thus Ha is accepted and H0 is rejected.